Evaluation Outcomes Associated with Alternative Dosing Strategies for Piperacillin/Tazobactam: A Systematic Review and Meta-Analysis - Hui Yang; Xiangli Cui; Zhuo Ma; Lihong Liu (Frontiers Media S.A., 2016)
A better dosing strategy can improve clinical outcomes for patients. We systematically reviewed the literatures to determine whether any clinical benefits exist for piperacillin/tazobactam by extended or continuous infusion. Methods - A search of PubMed, Web of Science, ProQuest, ScienceDirect, Cochrane, Embase and related ICAAC and ACCP conferences were conducted up to September 5, 2015. Randomized controlled and observational studies that compared extended or continuous infusion with conventional intermittent infusion of piperacillin/tazobactam were identified from the databases above and analyzed. Two reviewers independently evaluated the methodology and extracted data from primary studies. A meta-analysis was performed using Revman 5.2 software. The quality of each study was assessed. Sensitivity analysis and publication bias were evaluated. Results - Three randomized controlled trials and twelve observational studies were included in this study. All included studies had high quality and no publication bias was found. Compared to the conventional intermittent infusion approach, the extended or continuous infusion group had a significant cost effectiveness (OR -0.89.02, CI (-114.69,-63.35), P<0.00001). No statistical difference was observed for clinical cure rate (OR 1.64, 95% CI (0.88, 3.30), P=0.12) between the two dosing regimens. The sensitivity analysis showed the results were stable. Conclusions - Our systematic review and meta-analysis found that the outcomes associated with alternative dosing strategies of piperacillin/tazobactam have changed compared with conclusions before for several literatures with large samples published. Further data on the outcomes should be generated for a better understanding of the extended or continuous infusion strategy. On the whole, our meta-analysis suggested that the extended or continuous infusion should be recommended for clinical use only considering its economic advantage, but there was no significantly higher clinical cure rate and lower mortality rate compared with the conventional intermittent infusion.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.